Konsep Bantuan Hukum Dalam Perspektif Hukum Pidana Islam; Analisis Sosial-Historis - Mughiroh, Hafizul; Marpaung, Zaid Alfauza (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
This study examines the concept of legal aid in Islamic criminal law, focusing on the importance of ensuring fair and equal access to legal justice. Legal aid plays a crucial role in understanding individual rights within the context of Islamic law and ensuring that judicial processes align with the principles of Islamic justice. The research employs a qualitative method with a normative juridical approach. The findings reveal that the concept of legal aid in Islamic criminal law not only facilitates access to legal proceedings but also promotes social justice and the protection of human rights within the framework of Sharia. In the Islamic judicial system, defendants, victims, witnesses, prosecutors, and guardians all have equal rights to adequate legal assistance. Defendants are entitled to a fair defense in court, while victims and witnesses require legal protection for their rights. Prosecutors are responsible for providing appropriate legal aid to uphold fair law enforcement, and guardians ensure that justice is properly administered within society.